CUSTOMER SATISFACTION AS A MEDIATOR BETWEEN PERCEIVED QUALITY, ATTITUDES, AND READY-TO-DRINK COFFEE PURCHASE INTENTION - Edy Humaidi; Bina Unteawati; Nuni Anggraini; I Putu Adjie Windu Kertayoga; Rini Desfaryani (Universitas Garut, 2026)
Purchase intention is a key behavioral indicator of market competitiveness and business sustainability. Understanding its determinants—such as perceived quality, customer attitude, and satisfaction—is crucial for developing effective marketing strategies. This study analyzes the effects of perceived quality, customer attitude, and satisfaction on purchase intention for coffee ready-to-drink (RTD) products, and examines the mediating role of customer satisfaction. Data were collected through surveys and direct observation using accidental sampling, then analyzed with descriptive statistics and Structural Equation Modeling (SEM). The results show that customer attitude and satisfaction significantly influence purchase intention, both directly and through mediation. Customer satisfaction mediates the relationship between customer attitude and purchase intention, indicating that positive attitudes enhance satisfaction, which subsequently increases purchase intent. Conversely, perceived quality has no significant direct or indirect effect on purchase intention through satisfaction, suggesting its limited influence in this model. Overall, customer satisfaction serves as a key mediating factor linking attitude and purchase intention, while perceived quality plays a minor role. Strengthening customer attitudes and satisfaction is therefore a more effective strategy for increasing purchase intention for coffee RTD products.